Endomicrobium proavitum, the first isolate of Endomicrobia class. nov. (phylum Elusimicrobia) – an ultramicrobacterium with an unusual cell cycle that fixes nitrogen with a Group IV nitrogenase. (23rd July 2015) - Zheng, Hao; Dietrich, Carsten; Radek, Renate; Brune, Andreas
Summary: The bacterial tree contains many deep‐rooting clades without any cultured representatives. One such clade is 'Endomicrobia', a class‐level lineage in the phylum E lusimicrobia represented so far only by intracellular symbionts of termite gut flagellates. Here, we report the isolation and characterization of the first free‐living member of this clade from sterile‐filtered gut homogenate of defaunated (starch‐fed) R eticulitermes santonensis . Strain Rsa215 is a strictly anaerobic ultramicrobacterium that grows exclusively on glucose, which is fermented to lactate, acetate, hydrogen and CO2 . Ultrastructural analysis revealed a Gram‐negative cell envelope and a peculiar cell cycle. The genome contains a single set of nif genes that encode homologues of Group IV nitrogenases, which were so far considered to have functions other than nitrogen fixation. We documented nitrogenase activity and diazotrophic growth by measuring acetylene reduction activity and 15 N2 incorporation into cell mass, and demonstrated that transcription of nifH and nitrogenase activity occur only in the absence of ammonium. Based on the ancestral relationship to ' C andidatus  Endomicrobium trichonymphae' and other obligate endosymbionts, we propose the name ' E ndomicrobium proavitum ' gen. nov., sp. nov. for the first isolate of this lineage and the name ' E ndomicrobia ' class. nov. for the entire clade.